The level of participation of women with disabilities in economic empowerment programmes in Gweru District - Museva, Loveness (Scholarlink Research Institute Journals, 2016)
This study was carried to investigate the level of participation of women with disabilities in economic empowerment programmes in Gweru District. The objectives of the study were to find out community views on participation of women with disabilities and to examine barries that limited the participation of women with disabilities in economic programmes. The descriptive survey method was used to gather the data. Questionnaires and Interviews were used to solicit information from the thirty respondents in Gweru Urban. The researcher also gathered data from Government, Non-Governmental Organisations and Community Leaders. The study findings indicated that women with disabilities were given very little attention and not consulted in issues affecting their lives. Women with disabilities were regarded as charity cases. Cultural, Social, Physical and Psychological barriers were regarded as challenges that limited participation of women with disabilities in economic programmes. The study concluded that government and non-governmental organisations should craft new policies that would promote gender equality and advancement of women with disabilities. More support should be given by government, non-governmental organisations and community leaders to women with disabilities on issues that effect their lives.